2022
DOI: 10.3390/cryst12050633
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fly Ash Denitrification on Properties of Hybrid Alkali-Activated Composites

Abstract: This article deals with the possibility of partial replacement of blast furnace slag (GGBFS) with fly ash after denitrification (FAD) in alkali-activated materials. Physical-mechanical and durability properties were tested, hydration reaction was monitored, and infrared spectroscopy was performed. Results were compared between mixtures prepared with fly ash without denitrification (FA), and also with a mixture based only on GGBFS. The basic result is that hybrid alkali-systems with FAD show similar trends to F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Compared to the reference sample the flexural strength decreased by 7 to 41%, with fly ash content 20-60%. The results are in agreement with results of similar experiments [16,17]. An assessment of flexural strength was carried out and a frost resistance coefficient was calculated.…”
Section: Alkali Activated Bindersupporting
confidence: 87%
See 1 more Smart Citation
“…Compared to the reference sample the flexural strength decreased by 7 to 41%, with fly ash content 20-60%. The results are in agreement with results of similar experiments [16,17]. An assessment of flexural strength was carried out and a frost resistance coefficient was calculated.…”
Section: Alkali Activated Bindersupporting
confidence: 87%
“…Using Czech fly ashes after denitrification was tested in alkali-activated materials. Procházka [16,17] carried out an experimental study with fly ash from the power plant Ostrava-Třebovice. After denitrification an amount of ammonia was determined as 22.8 mg•kg -1 .…”
Section: Possibilities Of Using Fly Ashes After Denitrificationmentioning
confidence: 99%
“…Research has shown that fly ash from flue gas denitrification is characterized by a higher value of losses on ignition and ammonia content in comparison to ashes without denitrification; it has also been shown that the ammonia content in the analyzed range does not limit the use of fly ash as an additive to cement and concrete. Procházka et al [159] explained the influence of fly ash denitrification on the properties of hybrid alkali-activated composites. The purpose of this study was to evaluate the effect of SNCR denitrification on fly ash for usage in hybrid alkali-activated materials that were based on blast furnace granulated slag.…”
Section: Coal Fly Ashmentioning
confidence: 99%